A stress-relaxing hydrogel heart patch loaded with miR-210@zif-8, preparation method and application
Patent Information
- Application Number
- CN202611468599.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]综上,当前心脏补片技术普遍存在修复机制单一、性能与微环境适配性差、成型精度不足等技术瓶颈,无法有效协同调控心肌梗死后异常机械微环境刺激与缺氧线粒体代谢障碍这两大核心病理因素,导致心肌修复效果有限,抗纤维化能力不足,严重制约了心肌梗死修复的临床转化应用
[0028]由上可知,本发明提供的一种负载miR-210@ZIF-8的应力松弛水凝胶心脏补片,复合水凝胶基质为双交联网络结构,双交联网络结构包括可光交联高分子形成的光交联稳定网络,以及含醛基多糖与含氨基蛋白质通过动态席夫碱键构筑的动态交联网络;动态交联网络具备应力松弛与应力耗散特性,光交联稳定网络维持水凝胶心脏补片结构与尺寸稳定性,miR-210@ZIF-8纳米颗粒具有酸性响应释药特性,通过动态交联网络实现心肌梗死区域异常机械刺激的耗散与松弛,同时利用酸性响应释药特性在缺血微环境中靶向释放miR-210以调控线粒体功能,从而协同干预力学微环境与代谢障碍双重病理过程,具有能够协同调控心肌梗死后异常力学微环境与缺氧代谢障碍,有效抑制线粒体过度分裂,显著提升心肌修复效果和抗纤维化能力。
Smart Images

Figure CN122973706A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials and tissue engineering, and more specifically, to a stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8, its preparation method, and its application. Background Technology
[0002] Following myocardial infarction, the myocardial tissue remains in a state of ischemia and hypoxia, triggering fibrotic remodeling of the myocardial matrix, leading to an abnormally increased matrix stiffness and a significantly reduced stress dissipation capacity. This abnormally hardened mechanical microenvironment continuously acts on cardiomyocytes, stimulating the upregulation of Drp1 (dynein-associated protein 1) protein expression, inducing excessive mitochondrial division and fragmentation, causing irreversible damage to cardiomyocytes. Simultaneously, the ischemic and hypoxic microenvironment directly disrupts the stability of the mitochondrial membrane potential in cardiomyocytes, hindering ATP (adenosine triphosphate) synthesis, triggering energy metabolism disorders, and further exacerbating cardiomyocyte apoptosis, progressive thinning of the ventricular wall, and the process of myocardial fibrosis. This becomes the core pathological basis for the continuous deterioration of cardiac function and the development of heart failure after myocardial infarction. Therefore, achieving a dual synergistic intervention on the abnormal mechanical microenvironment and hypoxic metabolic disorders in the infarcted myocardial region is key to overcoming the current bottlenecks in myocardial repair technology.
[0003] In existing myocardial tissue engineering research, hydrogel cardiac patches have been widely used as an important repair strategy. However, the technical systems are mainly divided into two categories: mechanical support and single drug delivery, both of which have significant limitations. Mechanical support hydrogels generally adopt a single, stable covalently cross-linked network structure. Their mechanical properties are rigid, lacking dynamic response capabilities, and can only provide passive static support. These hydrogels cannot achieve controllable stress relaxation and stress dissipation functions, making it difficult to effectively dissipate the continuous abnormal mechanical stimulation generated by the sclerotic matrix after myocardial infarction. Therefore, they cannot inhibit the excessive mitochondrial division induced by mechanical stress at the source, resulting in a single mechanical repair mode with poor adaptability to the dynamically changing myocardial microenvironment, fundamentally limiting the repair effect.
[0004] To address myocardial hypoxia-induced metabolic damage, existing technologies attempt to regulate cardiomyocyte hypoxia adaptation and mitochondrial function by delivering miR210 (microRNA-210) molecules. However, free miR-210 exhibits extremely low stability in vivo, is readily degraded by tissue nucleases, and suffers from low cellular uptake efficiency, often remaining in intracellular bodies or lysosomes, making it difficult to release into the cytoplasm to exert its biological functions. While ZIF-8 (zeolite imidazolate backbone-8) nanocarriers loaded with miR-210 can provide nucleic acid protection and improve intracellular delivery efficiency, enabling drug release in response to an acidic microenvironment, such systems focus solely on improving cardiomyocyte metabolic function, completely neglecting the regulation of the abnormal mechanical microenvironment in the infarcted region. They fail to address the problem of mechanical stress-mediated myocardial injury, exhibiting serious shortcomings such as a one-sided repair mechanism and an inability to synergistically intervene in dual pathological defects.
[0005] In terms of molding technology, traditional mold-forming methods struggle to precisely control the shape, thickness distribution, and internal pore structure of cardiac patches, resulting in poor product uniformity and low individual adaptability, failing to meet the needs of individualized clinical repair. While digital light processing 3D printing technology can achieve high-precision structural molding of materials, existing composite hydrogel matrices face significant challenges in simultaneously achieving multiple performance aspects, including printing stability, dynamic stress relaxation mechanical properties, uniform loading of nano-active factors, and responsive drug release. To date, an integrated myocardial repair patch system capable of integrating mechanical microenvironment regulation, mitochondrial metabolic regulation, and high-precision controllable molding has not yet been developed.
[0006] In summary, current cardiac patch technology generally suffers from technical bottlenecks such as a single repair mechanism, poor performance and microenvironment compatibility, and insufficient molding precision. It cannot effectively coordinate and regulate the two core pathological factors of abnormal mechanical microenvironment stimulation and hypoxic mitochondrial metabolic disorders after myocardial infarction, resulting in limited myocardial repair effects and insufficient anti-fibrotic capacity, which seriously restricts the clinical translation and application of myocardial infarction repair.
[0007] To address the aforementioned issues, existing technologies urgently need improvement. Summary of the Invention
[0008] One objective of this invention is to provide a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8, combined with a printable hydrogel bio-ink, which can synergistically regulate the abnormal mechanical microenvironment and hypoxic metabolic disorders after myocardial infarction, effectively inhibit excessive mitochondrial division, and significantly improve myocardial repair and anti-fibrotic capabilities. miR210@ZIF-8 refers to ZIF-8-loaded microRNA-210 nanoparticles.
[0009] The above-mentioned objective of the present invention is a stress relaxation hydrogel heart patch loaded with miR-210@ZIF-8, which is specifically formed by 3D printing of hydrogel bio-ink. The hydrogel bio-ink includes a composite hydrogel matrix and miR-210@ZIF-8 nanoparticles, with the miR-210@ZIF-8 nanoparticles uniformly distributed inside the composite hydrogel matrix.
[0010] The composite hydrogel matrix is configured with a dual cross-linked network structure, comprising a stable cross-linked network and a dynamic cross-linked network. The stable cross-linked network is formed by photocrosslinkable polymer polymerization to maintain the overall structural and dimensional stability of the cardiac patch. The dynamic cross-linked network is constructed from aldehyde-containing polysaccharides and amino-containing proteins through dynamic Schiff base bonds. The photocrosslinkable polymer is methacrylamide hyaluronic acid, with the aforementioned miR-210@ZIF-8 nanoparticles uniformly distributed within it. The aldehyde-containing polysaccharide is oxidized dextran, and the amino-containing protein is gelatin. Preferably, the above-mentioned composite hydrogel matrix further comprises a photoinitiator LAP. LAP refers to lithium phenyl-2,4,6-trimethylbenzoylphosphinate.
[0011] miR-210@ZIF-8 nanoparticles are configured as regular polyhedral particles formed by the self-assembly of zinc ions and 2-methylimidazole, with a particle size distribution range of 140–220 nm and a surface potential of -13 mV ± 2 mV.
[0012] Preferably, the miR-210@ZIF-8 nanoparticles are provided with miR-210 and ZIF-8 nanoparticles, with miR-210 coating the ZIF-8 nanoparticles; and the ZIF-8 nanoparticles are uniformly distributed in the methacrylamide hyaluronic acid.
[0013] Another object of the present invention is to provide a method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8 as described above, comprising the following steps: S1. Methacrylamide hyaluronic acid, oxidized dextran, and miR-210@ZIF-8 nanoparticles were prepared separately, and deionized water was used to prepare 5% w / v methacrylamide hyaluronic acid solution and 10% w / v oxidized dextran solution, respectively.
[0014] S2. Preparation of sterile printable hydrogel bio-ink: A step-by-step feeding process was adopted. miR-210@ZIF-8 nanoparticles were uniformly dispersed in a methacrylamide hyaluronic acid solution to obtain pre-dissolved solution 1. Gelatin solution was added to pre-dissolved solution 1 under constant temperature T1 and mixed to obtain pre-dissolved solution 2. Photoinitiator solution was added to pre-dissolved solution 2 under light-protected conditions and stirred to obtain pre-dissolved solution 3. Finally, oxidized dextran solution was quickly added to pre-dissolved solution 3 and mixed to obtain hydrogel bio-ink. S3. Digital light processing 3D printing molding: The hydrogel bio-ink is stereolithographically cured and 3D printed using digital light processing 3D printing equipment. After molding, it is washed with sterile deionized water to remove uncrosslinked impurities, resulting in a stress-relaxed hydrogel heart patch.
[0015] Specifically, the preparation method of methacrylamide hyaluronic acid in step S1 above is as follows: S1A-1, prepare a hyaluronic acid solution with a mass-volume concentration of 1% by dissolving sodium hyaluronate in deionized water; S1A-2, after adjusting the pH value to pH 8.0 to pH 9.0 by stirring the hyaluronic acid solution in an ice bath, add methacrylic anhydride dropwise within the reaction time S. After the addition is completed, continue the reaction at 4℃ for 24h to allow the hydroxyl groups on the hyaluronic acid molecular chain to undergo an esterification reaction with methacrylic anhydride to produce a photocrosslinkable methacryloyl reaction solution. S1A-3: Add sodium chloride to the methacrylyl reaction solution until the final concentration of sodium chloride reaches 0.5 mol / L, then terminate the reaction to obtain a termination reaction mixture. Slowly add the termination reaction mixture to 5 times the volume of pre-cooled anhydrous ethanol, stir thoroughly, and let stand for 30 min to allow methacrylylated hyaluronic acid to precipitate. Collect the precipitate by centrifugation at 5000×g for 5 min, and wash twice with pre-cooled anhydrous ethanol to obtain the preliminary precipitate acid. S1A-4, the preliminary precipitated acid is redissolved in deionized water and dialyzed through dialysis bag 1 to obtain preliminary dialysis acid. The preliminary dialysis acid is pre-frozen at -80℃ and then freeze-dried to obtain white spongy methacrylamide hyaluronic acid.
[0016] Specifically, the preparation method of oxidized dextran in step S1 above is as follows: S1B-1, prepare a dextran solution with a mass-volume concentration of 100 g / L and a sodium periodate solution with a mass-volume concentration of 100 g / L respectively; S1B-2, under light-protected conditions, sodium periodate solution was slowly added dropwise to dextran solution, and the reaction was carried out at room temperature for 4 hours to obtain a preliminary aldehyde reaction solution; S1B-3, the initial aldehyde reaction solution is added to a corresponding 1 / 15 volume of ethylene glycol solution, and the oxidation reaction is terminated by stirring to obtain an initial solution containing oxidized dextran powder. The initial solution containing oxidized dextran powder is placed into dialysis bag 2 for dialysis treatment. After the dialysis is completed, the dialysis concentrate is obtained. The dialysis concentrate is pre-frozen at -80°C and freeze-dried to obtain oxidized dextran powder in powder form.
[0017] Sodium periodate solution was slowly added dropwise to dextran solution, with the ratio of sodium periodate to dextran set at 1:7.6 w / w to 1:3.8 w / w; Specifically, the preparation method of miR-210@ZIF-8 nanoparticles in step S1 above is as follows: S1C-1, using water treated with diethyl pyrocarbonate, prepared 40 mmol / L zinc acetate solution and 1.28 mol / L 2-methylimidazole solution respectively.
[0018] For S1C-2, according to the volume ratio, take 10 times the volume of a 40 mmol / L zinc acetate solution and add 1 volume of a 20 μmol / L miR-210 solution. After gently mixing, incubate at room temperature for 10 minutes to form Zn. 2+ It interacts electrostatically with the negatively charged phosphate backbone of miR-210 and forms a mixture of nucleation sites.
[0019] S1C-3, under rapid stirring, a 1:1 volume of 1.28 mol / L 2-methylimidazole solution is quickly added to the mixture to form reaction solution C-3. The molar ratio of zinc acetate to 2-methylimidazole is 1:32.
[0020] While waiting for the appearance of turbidity in the C-3 reaction solution, indicating the beginning of the formation of the ZIF-8 coordination structure, the C-3 reaction solution was allowed to stand at room temperature for 20 minutes to form a preliminary coated nano-liquid that allows miR-210 to be simultaneously coated during the formation of ZIF-8.
[0021] In step S1C-4, the initially coated nanofluid obtained after the reaction was centrifuged at 12,000 rpm for 15 min, the supernatant was discarded, and the precipitate was resuspended in water treated with diethyl pyrocarbonate and washed three times to obtain miR-210@ZIF-8 nanoparticles. The purpose of this step was to remove free miR-210, unreacted zinc ions, and 2-methylimidazole.
[0022] Preferably, the preparation method of methacrylamide hyaluronic acid in step S1 is as follows: the final concentration of miR-210@ZIF-8 in the hydrogel bio-ink in step S2 is 0.1-1.0 mg / mL; preferably, the isothermal temperature T1 condition is set to 34-40℃.
[0023] Preferably, the above-mentioned constant temperature (T1) condition is set to 37°C; Preferably, the concentration of the photoinitiator solution in S2 is 2.5% w / v; Preferably, in step S2 above, the final concentration of methacrylamide hyaluronic acid in the hydrogel bio-ink is 2.5% w / v, the final concentration of gelatin in the hydrogel bio-ink is 3.0% w / v, the final concentration of oxidized dextran in the hydrogel bio-ink is 1.0% w / v, the final concentration of photoinitiator in the hydrogel bio-ink is 0.25% w / v, and the final concentration of miR-210@ZIF-8 nanoparticles in the hydrogel bio-ink is 0.5 mg / mL. Preferably, the molecular weight cutoff of the dialysis bag 1 is 3500-8000 Da; the reaction time S is 1.5H to 2.5H. Preferably, the reaction time S is 2H.
[0024] Preferably, the dialysis bag 1 is subjected to dialysis in deionized water for 4 days, with the dialysis solution being replaced every 8-12 hours. Preferably, the dialysis bag 2 is subjected to dialysis treatment by placing it in a dialysis bag 2 with a molecular weight cutoff of 3500-8000 Da, dialyzing it in deionized water in the dark for 3 days, and changing the dialysis solution 4 times a day.
[0025] Preferably, the preparation method of oxidized dextran in step S1 further includes S1B-4, which involves storing the oxidized dextran powder in a light-proof and sealed manner.
[0026] Preferably, the method for preparing methacrylamide hyaluronic acid in step S1 above further includes step S1A-5, which involves sealing and storing the methacrylamide hyaluronic acid at -20°C.
[0027] Another object of the present invention is to provide the use of the stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8 in the preparation of medical materials for myocardial infarction repair or anti-myocardial fibrosis drugs.
[0028] As can be seen from the above, the present invention provides a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8. The composite hydrogel matrix has a double cross-linked network structure, which includes a photocrosslinking stable network formed by photocrosslinkable polymers and a dynamic cross-linked network constructed by aldehyde-containing polysaccharides and amino-containing proteins through dynamic Schiff base bonds. The dynamic cross-linked network has stress relaxation and stress dissipation characteristics, the photocrosslinking stable network maintains the structural and dimensional stability of the hydrogel cardiac patch, and the miR-210@ZIF-8 nanoparticles have acid-responsive drug release characteristics. Through the dynamic cross-linked network, the abnormal mechanical stimulation in the myocardial infarction area is dissipated and relaxed. At the same time, the acid-responsive drug release characteristics are used to target and release miR-210 in the ischemic microenvironment to regulate mitochondrial function, thereby synergistically intervening in the dual pathological processes of mechanical microenvironment and metabolic disorders. It has the ability to synergistically regulate the abnormal mechanical microenvironment and hypoxic metabolic disorders after myocardial infarction, effectively inhibit excessive mitochondrial division, and significantly improve myocardial repair effect and anti-fibrotic ability. Attached Figure Description
[0029] Figure 1 This figure shows the abnormal mechanical microenvironment characteristics of myocardial infarction and its impact on Drp1 expression in cardiomyocytes; among them... Figure 1 A in Figure 1 In the diagrams, B represents the gross morphology of the myocardium in rats from the Sham and MI groups, respectively. Figure 1 C in Figure 1 The D in the figure represents a statistical comparison of Young's modulus and stress relaxation time between normal myocardium and infarcted myocardium. Figure 1 E in the figure represents the Western blot results of Col1A1 and α-SMA protein, markers of myocardial fibrosis. Figure 1 F in the diagram represents a basal cell culture model with different stiffnesses using PDMS. Figure 1 G in the figure represents a statistical comparison of Young's modulus for different soft and hard PDMS substrates; Figure 1 H in Figure 1 The figure I in the figure represents the results of detecting the mRNA and protein expression levels of Drp1 in cardiomyocytes on substrates with different stiffness.
[0030] Figure 2 Figures show the material characterization and mitochondrial protection effects of hydrogels with different stress relaxation properties; among them, Figure 2 In the diagram, A represents a schematic image of the hydrogel synthesis process. Figure 2 In the image, B is the Fourier transform infrared spectrum of the hydrogel. The left side shows the appearance of the hydrogel before molding, and the right side shows the appearance of the hydrogel after molding. Figure 2 C in the figure represents the initial elastic modulus test results of the three groups of hydrogels; Figure 2 D in the figure represents the stress relaxation rheological test curves of three groups of hydrogels; Figure 2E in the figure represents the results of Drp1 mRNA expression detection in three groups of cardiomyocytes cultured on hydrogel surfaces; Figure 2 Figure F in the figure shows the results of Drp1 protein expression detection on the surface of three groups of cardiomyocytes cultured on hydrogels; Figure 2 G in Figure 2 H in the figure represents the mitochondrial fluorescence image and the quantitative statistical results of fragmentation.
[0031] Figure 3 Structural characterization of a DLP-3D printed stress-relaxed hydrogel cardiac patch; among which, Figure 3 In the diagram, A represents the three-dimensional model of the hydrogel heart patch and a schematic diagram of its DLP printing process. Figure 3 B in Figure 3 C in the image represents the macroscopic morphology of a 3D-printed mesh-like hydrogel heart patch. Figure 3 D in the image represents a scanning electron microscope (SEM) image of the microscopic porous structure inside the hydrogel patch.
[0032] Figure 4 Figures show the physicochemical characterization and intracellular delivery properties of miR-210@ZIF-8 nanoparticles; among them, Figure 4 In the diagram, A represents the principle of in-situ loading preparation of miR-210@ZIF-8; Figure 4 B in the image represents electron micrographs of blank ZIF-8 and miR-210@ZIF-8. Figure 4 C in the figure represents the surface potential detection results of the two types of nanoparticles; Figure 4 In the figure, D represents the statistical distribution of nanoparticle size. Figure 4 Figure E in the diagram illustrates how ZIF-8 enables miR210 to escape from lysosomes. Figure F shows the lysosomal colocalization fluorescence and colocalization coefficient statistics at different time points after cardiomyocytes take up free miR-210 and ZIF-8-encapsulated miR-210, respectively.
[0033] Figure 5 The diagram shows the protective effect of miR-210@ZIF-8 on mitochondrial function in hypoxic cardiomyocytes; among them, Figure 5 A in Figure 5 In the figure, C represents the JC-1 fluorescence staining image of mitochondrial membrane potential in cardiomyocytes of each group and its quantitative statistical results; Figure 5 B in the image represents the EdU proliferation staining detection results for cardiomyocytes in each group. Figure 5 D in the figure represents the statistical graph of ATP content detection in cardiomyocytes of each group.
[0034] Figure 6 The image shows the effect of composite hydrogel cardiac patches on improving myocardial injury and fibrosis in rats with myocardial infarction; among them... Figure 6 In the image, A represents a pathological section of myocardial tissue stained with H&E (hematoxylin and eosin) in each group; Figure 6B in the image represents Masson fibrosis stained sections of myocardial tissue from each group. Figure 6 C in the graph represents the statistical analysis of cardiac ejection fraction in each group of rats; Figure 6 D in the figure represents the statistical graph of the heart shortening fraction of each group of rats. Detailed Implementation
[0035] The technical solution of the present invention will be described below with reference to the accompanying drawings and embodiments.
[0036] Example 1 A stress-relaxation hydrogel heart patch loaded with miR-210@ZIF-8 is formed by 3D printing from hydrogel bio-ink. The hydrogel bio-ink includes a composite hydrogel matrix and miR-210@ZIF-8 nanoparticles, with the miR-210@ZIF-8 nanoparticles uniformly distributed within the composite hydrogel matrix.
[0037] Specifically, the aforementioned composite hydrogel matrix is configured as a double cross-linked network structure composite hydrogel matrix, which includes a cross-linking stable network and a dynamic cross-linking network. The cross-linking stable network is formed by photocrosslinkable polymer polymerization to maintain the overall structural and dimensional stability of the cardiac patch, and the dynamic cross-linking network is constructed by aldehyde-containing polysaccharides and amino-containing proteins through dynamic Schiff base bonds.
[0038] The photocrosslinkable polymer is set as methacrylamide hyaluronic acid, and the above miR-210@ZIF-8 nanoparticles are uniformly distributed in the methacrylamide hyaluronic acid; the aldehyde-containing polysaccharide is oxidized dextran, and the amino-containing protein is gelatin. Specifically, the aforementioned composite hydrogel matrix also contains the photoinitiator LAP.
[0039] Specifically, the miR-210@ZIF-8 nanoparticles are configured as regular polyhedral particles formed by the coordination self-assembly of zinc ions and 2-methylimidazole, with a particle size distribution range of 140–220 nm and a surface potential of -13 mV ± 2 mV.
[0040] Specifically, the miR-210@ZIF-8 nanoparticles contain miR-210 and ZIF-8 nanoparticles, with miR-210 coating the ZIF-8 nanoparticles; the ZIF-8 nanoparticles are uniformly distributed in methacryloyl hyaluronic acid.
[0041] The aforementioned photocrosslinking stabilizing network maintains the overall structural and dimensional stability of the cardiac patch, while the dynamic crosslinking network endows the hydrogel with excellent stress relaxation and stress dissipation properties. miR-210@ZIF-8 nanoparticles are uniformly distributed within the composite hydrogel matrix, exhibiting acid-responsive drug release characteristics. The cardiac patch, through the stress relaxation properties of the composite hydrogel matrix, reduces the continuous mechanical stimulation of cardiomyocytes by the hardened matrix, inhibiting Drp1 (dynein-associated protein 1)-mediated excessive mitochondrial division. Simultaneously, miR-210 improves the decrease in mitochondrial membrane potential, insufficient ATP production, and energy metabolism disorders caused by ischemia and hypoxia, thereby synergistically maintaining the structural and functional homeostasis of cardiomyocyte mitochondria.
[0042] To clearly explain the technical solution of this invention, the key terms in this embodiment are defined and explained: The dual-crosslinked network structure refers to a three-dimensional polymer network constructed by two different crosslinking mechanisms simultaneously existing in the composite hydrogel matrix. Specifically, this invention is an interpenetrating polymer system formed by the interpenetration of a photocrosslinked covalently stable network and a dynamic Schiff base bond reversible network, possessing both structural stability and dynamic mechanical adaptive characteristics. The dynamic Schiff base bond refers to a reversible imine bond formed by the nucleophilic addition and dehydration of a nucleophilic amino group and an aldehyde group. This chemical bond can continuously undergo a dynamic equilibrium of breakage and recombination in an aqueous physiological environment, which is the core basis for achieving the stress relaxation performance of the material. Stress relaxation and stress dissipation refer to the mechanical response characteristics of the material's internal stress decaying over time under constant strain, and the energy dissipation behavior of converting mechanical energy into heat energy through dynamic bond breakage and recombination and molecular chain slippage under alternating mechanical loads on the heart, which can effectively buffer abnormal mechanical stimulation. miR-210@ZIF-8 nanoparticles refer to a nanoscale drug delivery system formed by encapsulating miR-210 nucleic acid molecules with hypoxia metabolism regulation activity during crystal nucleation and growth, using a porous metal-organic framework formed by the self-assembly of zinc ions and 2-methylimidazole as a carrier. It possesses good biocompatibility and acid-responsive drug release performance.
[0043] The following details the specific implementation methods and technical principles of the core technical features of the hydrogel cardiac patch of this invention: The construction of the photocrosslinking stable network involves using a water-soluble photosensitive polymer precursor to prepare an aqueous solution. Under the action of a photoinitiator, free radicals are generated by visible or ultraviolet light irradiation, initiating the polymerization and crosslinking of the polymer's carbon-carbon double bonds. This forms a dense covalently crosslinked framework with good elastic recovery capabilities, providing stable structural support and resistance to deformation for the overall hydrogel. The construction of the dynamic crosslinking network involves uniformly mixing an aldehyde-containing water-soluble polysaccharide solution with a protein solution rich in free amino groups in a proportional manner. In a near-neutral, mild aqueous environment at room temperature, the aldehyde groups and free amino groups spontaneously undergo a condensation reaction, forming a large number of reversible dynamic Schiff base bonds, thus constructing a dynamic crosslinking network that runs through the entire composite hydrogel matrix. The uniform composite of miR-210@ZIF-8 nanoparticles is achieved by sequentially mixing and stirring the nanoparticle dispersion with the photocrosslinking precursor solution and the functional polymer solution. This ensures that the nanoparticles are stably embedded inside the hydrogel matrix, preventing particle aggregation and loss, and guaranteeing stable drug release.
[0044] This invention's hydrogel cardiac patch achieves dual pathological microenvironment repair through the synergistic effect of two networks: a photocrosslinked stable network can withstand the reciprocating mechanical loads of the heart's periodic contraction and relaxation, maintaining the macroscopic shape integrity and dimensional stability of the patch after implantation; a dynamic network composed of dynamic Schiff base bonds can dissipate abnormal mechanical stress generated by the infarcted sclerotic matrix in real time, eliminating mitochondrial excessive division damage caused by mechanical stimulation; and dispersed miR-210@ZIF-8 nanoparticles can respond to the weakly acidic microenvironment of the infarcted area by structural dissociation, continuously releasing miR-210 active nucleic acid molecules, regulating mitochondrial energy metabolism in cardiomyocytes, alleviating hypoxia-induced apoptosis, and ultimately achieving a synergistic effect of mechanical microenvironment remodeling and metabolic function repair.
[0045] The photocrosslinkable polymer is methacrylamide hyaluronic acid, the aldehyde-containing polysaccharide is oxidized dextran, and the amino-containing protein is gelatin. Methacrylamide hyaluronic acid is a photosensitive modified derivative of natural hyaluronic acid, endowed with photopolymerization activity by grafting methacryl groups onto the molecular backbone. This material possesses excellent hydrophilicity, biocompatibility, and rapid photocrosslinking ability. After light exposure, it can form a dense and uniform covalent network, providing a stable mechanical support framework for the hydrogel, effectively resisting in vivo mechanical fatigue, and preventing patch deformation, breakage, or detachment. Oxidized dextran is a multi-aldehyde macromolecular crosslinking agent obtained by selectively oxidizing natural dextran. Through periodate oxidation, active aldehyde groups can be uniformly introduced onto the sugar chain. It has high reactivity and good molecular chain flexibility, providing sufficient and uniform reaction sites for the construction of dynamic Schiff base bonds, and precisely controlling the crosslinking density of the dynamic network. Gelatin, a hydrolysate of collagen, not only retains natural cell adhesion recognition sequences and possesses excellent biocompatibility and degradability, but is also rich in lysine free amino groups, serving as a stable amino donor. It undergoes reversible cross-linking with the aldehyde groups of oxidized dextran, stably constructing a dynamic adaptive network and effectively promoting cardiomyocyte adhesion and proliferation. The dual-crosslinking system synergistically constructed from these three natural modified polymers achieves a precise balance between mechanical properties and biological functions: the photocrosslinking network ensures long-term structural stability, the dynamic Schiff base bond network enables adaptive stress dissipation, and the homogeneous hydrophilic matrix environment ensures uniform dispersion of miR-210@ZIF-8 nanoparticles, preventing particle sedimentation and aggregation, and stably performing acid-responsive drug release and metabolic regulation functions.
[0046] miR-210@ZIF-8 nanoparticles are physically dispersed and embedded within a double-crosslinked network. The particles themselves do not participate in the chemical reactions of Schiff base bonds or photocrosslinking covalent bonds. However, under high loading, agglomerated particles can act as defect sites, disrupting the continuous network structure of the polymer chains. The nanoparticle loading concentration is a key parameter balancing drug release efficacy and material mechanical properties. Too low a concentration cannot achieve an effective therapeutic dose, while too high a concentration can easily lead to particle agglomeration and interfere with the hydrogel crosslinking structure. Therefore, this invention limits the loading concentration of miR-210@ZIF-8 nanoparticles in the composite hydrogel matrix to 0.1–1.0 mg / mL. This range ensures sufficient drug release from the infarct microenvironment, effectively improving myocardial hypoxia metabolism, while maintaining the integrity of the double-crosslinked network structure, thus balancing material mechanical properties and biorepair activity.
[0047] Example 2 A method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8, comprising the steps described in Example 1 above. S1. Methacrylamide hyaluronic acid, oxidized dextran, and miR-210@ZIF-8 nanoparticles were prepared separately, and deionized water was used to prepare 5% w / v methacrylamide hyaluronic acid solution and 10% w / v oxidized dextran solution, respectively.
[0048] S2. Preparation of sterile printable hydrogel bio-ink: A stepwise feeding process was used to uniformly disperse miR-210@ZIF-8 nanoparticles in a methacrylamide hyaluronic acid solution to obtain pre-dissolved solution 1; gelatin solution was added to pre-dissolved solution 1 at a constant temperature (T1) and mixed to obtain pre-dissolved solution 2; photoinitiator solution was added to pre-dissolved solution 2 under light-protected conditions and stirred to obtain pre-dissolved solution 3; finally, oxidized dextran solution was rapidly added to pre-dissolved solution 3 and mixed to obtain hydrogel bio-ink; the constant temperature (T1) was set to 34-40°C. In this embodiment, the constant temperature (T1) was set to 37°C. The final concentration of miR-210@ZIF-8 in the hydrogel bio-ink in S2 was 0.1–1.0 mg / mL. Specifically, the concentration of the photoinitiator solution in S2 above is 2.5% w / v; Specifically, in step S2 above, the final concentration of methacrylamide hyaluronic acid in the hydrogel bio-ink is 2.5% w / v, the final concentration of gelatin in the hydrogel bio-ink is 3.0% w / v, the final concentration of oxidized dextran in the hydrogel bio-ink is 1.0% w / v, the final concentration of photoinitiator in the hydrogel bio-ink is 0.25% w / v, and the final concentration of miR-210@ZIF-8 nanoparticles in the hydrogel bio-ink is 0.5 mg / mL. S3. Digital light processing 3D printing molding: The hydrogel bio-ink is stereolithographically cured and 3D printed using digital light processing 3D printing equipment. After molding, it is washed with sterile deionized water to remove uncrosslinked impurities, resulting in a stress-relaxed hydrogel heart patch.
[0049] In this example, DLP 3D printing technology was used to fabricate a regular mesh-like hydrogel heart patch using layer-by-layer photocuring of hydrogel bio-ink. During printing, the hydrogel bio-ink was added to the printing chamber, and the patch was formed through layer-by-layer photocuring. In this embodiment, the layer thickness was set to 0.05 mm, the planar dimensions were 10 mm × 10 mm, the target thickness was approximately 2 mm, the number of layers was 35, the photocuring time for each layer was 20 seconds, the interlayer settling time was 3 seconds, and the bottom layer consisted of 3 layers. These settings can be adjusted according to the specific product requirements during actual production printing. DLP is a surface-exposure photocuring 3D printing process and one of the most commonly used molding methods for bio-3D printing hydrogel scaffolds.
[0050] Methacrylamide hyaluronic acid forms a stable photocrosslinking network under the action of a photoinitiator, which is used to maintain the overall morphology, printing accuracy, and mechanical stability of the hydrogel patch. The aldehyde groups on the oxidized dextran molecular chain form reversible Schiff base bonds with the amino groups on the gelatin molecular chain, constituting a crosslinking network capable of dynamic breakage, exchange, and recombination, thereby endowing the hydrogel with stress relaxation and stress dissipation properties. Gelatin can also provide cell adhesion sites and endow the hydrogel with a certain matrix metalloproteinase-responsive degradation ability.
[0051] Specifically, the preparation method of methacrylamide hyaluronic acid in step S1 above is as follows: S1A-1, prepare a hyaluronic acid solution with a mass-volume concentration of 1% by dissolving sodium hyaluronate in deionized water; S1A-2, after adjusting the pH value to pH 8.0 to pH 9.0 by stirring the hyaluronic acid solution in an ice bath, add methacrylic anhydride dropwise within the reaction time S. After the addition is completed, continue the reaction at 4℃ for 24h to allow the hydroxyl groups on the hyaluronic acid molecular chain to undergo an esterification reaction with methacrylic anhydride to produce a photocrosslinkable methacryloyl reaction solution. S1A-3: Add sodium chloride to the methacrylyl reaction solution until the final concentration of sodium chloride reaches 0.5 mol / L, then terminate the reaction to obtain a termination reaction mixture. Slowly add the termination reaction mixture to 5 times the volume of pre-cooled anhydrous ethanol, stir thoroughly, and let stand for 30 min to allow methacrylylated hyaluronic acid to precipitate. Collect the precipitate by centrifugation at 5000×g for 5 min, and wash twice with pre-cooled anhydrous ethanol to obtain the preliminary precipitate acid. S1A-4, the preliminary precipitated acid is redissolved in deionized water and dialyzed through dialysis bag 1 to obtain preliminary dialysis acid. The preliminary dialysis acid is pre-frozen at -80℃ and then freeze-dried to obtain white spongy methacrylamide hyaluronic acid.
[0052] The molecular weight cutoff of the dialysis bag 1 is 3500-8000 Da; the reaction time S is 1.5H to 2.5H. In this embodiment, the reaction time S is 2H.
[0053] The dialysis bag 1 described above is specifically treated by dialysis in deionized water for 4 days, with the dialysis solution being changed every 8-12 hours. Specifically, the preparation method of oxidized dextran in step S1 above is as follows: S1B-1, prepare a dextran solution with a mass-volume concentration of 100 g / L and a sodium periodate solution with a mass-volume concentration of 100 g / L respectively; S1B-2, under light-protected conditions, sodium periodate solution was slowly added dropwise to dextran solution, and the reaction was carried out at room temperature for 4 hours to obtain a preliminary aldehyde reaction solution; S1B-3: The initial aldehyde reaction solution is added to a corresponding 1 / 15 volume of ethylene glycol solution. After terminating the stirring oxidation reaction, a preliminary solution containing oxidized dextran powder is obtained. This preliminary solution containing oxidized dextran powder is placed in dialysis bag 2 for dialysis. After dialysis, a concentrated dialysis solution is obtained. The concentrated dialysis solution is pre-frozen at -80°C and freeze-dried to obtain oxidized dextran powder in powder form. Specifically, the dialysis treatment in dialysis bag 2 involves placing the solution in a dialysis bag 2 with a molecular weight cutoff of 3500–8000 Da and dialyzing in deionized water in the dark for 3 days, changing the dialysis solution 4 times daily.
[0054] The preparation method of oxidized dextran in step S1 above also includes S1B-4, which involves storing the oxidized dextran powder in a light-proof and sealed container.
[0055] Sodium periodate solution was slowly added dropwise to dextran solution, with the ratio of sodium periodate to dextran set at 1:7.6 w / w to 1:3.8 w / w. The oxidation degree could be controlled within the range of 10%–20% by adjusting the amount of sodium periodate added during the dextran oxidation reaction. Oxidized dextran with different oxidation degrees was prepared by adjusting the amount of sodium periodate added during the dextran oxidation reaction.
[0056] In the construction of the dual crosslinking system, the concentration ratio of each component directly determines the crosslinking density, mechanical properties, printing stability, and nanoparticle loading uniformity of the hydrogel. An imbalance in the ratio will make it impossible to simultaneously achieve structural stability and stress relaxation characteristics. Therefore, this invention further specifies that the composite hydrogel matrix also contains the photoinitiator LAP, with the final concentration range of each component being: 2.0–3.0% w / v of methacryloyl hyaluronic acid, 2.0–4.0% w / v of gelatin, 0.8–1.2% w / v of oxidized dextran, and 0.2–0.3% w / v of photoinitiator LAP. Controlling the concentration of methacryloyl hyaluronic acid within this range provides sufficient photocrosslinking reaction sites while maintaining suitable precursor flowability. This avoids both excessively low concentrations leading to a sparse crosslinking network and insufficient mechanical strength, and excessively high concentrations causing excessive system viscosity and poor printability. The gelatin concentration range provides sufficient free amino groups, ensuring stable formation of dynamic Schiff base bonds, while preventing premature physical gelation at room temperature, thus ensuring the uniformity and stability of the system preparation and printing process. The concentration of oxidized dextran can be precisely matched to the amino content, regulating the dynamic cross-linking reaction kinetics and adapting to the overall molding process window. Within this low-toxicity concentration range, the water-soluble LAP photoinitiator can efficiently initiate the photopolymerization reaction, ensuring sufficient cross-linking while completely avoiding the cytotoxic risks associated with high-concentration initiators. This composition ratio achieves a synergistic balance between the cross-linking density of the photocrosslinked rigid network and the dynamically reversible network, enabling the hydrogel to possess both fatigue-resistant structural stability and controllable stress relaxation properties. This allows it to adapt to the dynamic mechanical environment of the heart while ensuring uniform dispersion of nanoparticles, providing a stable material basis for the synergistic repair of the myocardial pathological microenvironment.
[0057] The oxidation degree of oxidized dextran directly determines the aldehyde content of the molecular chain, which is a core parameter for regulating the dynamic Schiff base bond density and controlling the stress relaxation performance of hydrogels. Increased oxidation degree leads to more aldehyde sites on each polysaccharide chain that can participate in the reaction, allowing for the formation of more dynamic Schiff base bonds with gelatin amino groups, thus increasing the cross-linking density of the dynamic network. Insufficient oxidation results in a sparse dynamic cross-linking network and insufficient stress dissipation capacity; excessive oxidation causes overly dense cross-linking, restricting molecular chain slippage and resulting in a loss of dynamic mechanical adaptability. Therefore, this invention limits the oxidation degree of oxidized dextran to 10%–20%, a range that precisely balances the cross-linking strength and dynamic reversibility of the dynamic network, achieving a high degree of adaptability to the myocardial contractile dynamics environment.
[0058] To further achieve the optimal synergistic effect of mechanical repair and metabolic regulation, this invention provides an optimal and precise formulation: the preferred final concentrations of each component are: 2.5% w / v methacrylamide hyaluronic acid, 3.0% w / v gelatin, 1.0% w / v oxidized dextran with 20% oxidation degree, and 0.25% w / v photoinitiator LAP; the preferred loading concentration of miR-210@ZIF-8 nanoparticles is 0.5 mg / mL. This optimal formulation enables precise matching of multiple parameters: the 0.5 mg / mL nanoparticles achieve stable dispersion without aggregation, providing a long-lasting and balanced miR-210 release flux; the precise ratio of 20% high-oxidation-degree oxidized dextran and gelatin constructs a highly sensitive and reversible dynamic Schiff base network, maximizing the dissipation of abnormal mechanical stress; the moderate concentration of photocrosslinking components ensures the precision of patch molding and structural stability; and the low dose of LAP ensures biocompatibility, ultimately achieving the best synergistic effect of mechanical microenvironment remodeling and mitochondrial metabolic repair.
[0059] The particle size, morphology, and surface potential of nanoparticles directly determine their dispersion stability, cellular uptake efficiency, and drug release controllability. Therefore, this invention specifies that the miR-210@ZIF-8 nanoparticles are regular polyhedral particles formed by the self-assembly of zinc ions and 2-methylimidazole, with a particle size distribution range of 140–220 nm and a surface potential of -13 mV ± 2 mV. The regular crystalline framework provides physical shielding protection for the internally encapsulated miR-210, effectively resisting degradation by nucleases in vivo and ensuring stable nucleic acid activity. The moderate particle size of 140–220 nm ensures stable intercalation of the particles within the hydrogel network, preventing leakage and aggregation. The moderately negative surface potential enhances the colloidal stability of the particles, promotes efficient endocytosis by cardiomyocytes, and ensures stable metabolic regulation.
[0060] Traditional molded hydrogel patches suffer from a single structure and poor adaptability, failing to match individualized myocardial defect morphology. Furthermore, their disordered internal pore structure hinders nutrient exchange and cell infiltration. To address this, this invention employs a digital light processing (DLP) 3D printing integrated molding process to fabricate a hydrogel cardiac patch with a multi-level porous mesh structure. The macroscopic mesh pore size is 0.5–2.0 mm, the microscopic porous channel pore size is 10–100 μm, and the porosity is 60%–90%. DLP 3D printing enables precise customization of the patch's shape, thickness, and pore structure, overcoming the limitations of traditional molding processes. The large macroscopic mesh pores enhance the patch's flexibility and pulsatile compliance, closely conforming to myocardial movement and dispersing mechanical tension. The interconnected microscopic porous channels accelerate nutrient delivery and metabolic waste removal, while providing ample space for cell adhesion and infiltration, and acid-responsive drug release and diffusion of nanoparticles, achieving a synergistic effect of structural adaptation, mechanical buffering, and biological repair.
[0061] Specifically, the preparation method of miR-210@ZIF-8 nanoparticles in step S1 above is as follows: S1C-1, using water treated with diethyl pyrocarbonate, prepared 40 mmol / L zinc acetate solution and 1.28 mol / L 2-methylimidazole solution respectively.
[0062] For S1C-2, according to the volume ratio, take 10 times the volume of a 40 mmol / L zinc acetate solution and add 1 volume of a 20 μmol / L miR-210 solution. After gently mixing, incubate at room temperature for 10 minutes to form Zn. 2+ It interacts electrostatically with the negatively charged phosphate backbone of miR-210 and forms a mixture of nucleation sites.
[0063] S1C-3, under rapid stirring, a 1:1 volume of 1.28 mol / L 2-methylimidazole solution is quickly added to the mixture to form reaction solution C-3. The molar ratio of zinc acetate to 2-methylimidazole in reaction solution C-3 is 1:32.
[0064] While waiting for the appearance of turbidity in the C-3 reaction solution, indicating the beginning of the formation of the ZIF-8 coordination structure, the C-3 reaction solution was allowed to stand at room temperature for 20 minutes to form a preliminary coated nano-liquid that allows miR-210 to be simultaneously coated during the formation of ZIF-8.
[0065] In step S1C-4, the initially coated nanofluid obtained after the reaction was centrifuged at 12,000 rpm for 15 min, the supernatant was discarded, and the precipitate was resuspended in water treated with diethyl pyrocarbonate and washed three times to obtain miR-210@ZIF-8 nanoparticles. The purpose of this step was to remove free miR-210, unreacted zinc ions, and 2-methylimidazole.
[0066] The preparation method of methacrylamide hyaluronic acid in step S1 above also includes S1A-5, which involves sealing and storing the methacrylamide hyaluronic acid at -20°C.
[0067] miR-210 is a hypoxia-associated microRNA that participates in cellular hypoxia adaptation, mitochondrial metabolic regulation, and cell survival. Encapsulating miR-210 in ZIF-8 nanoparticles reduces the risk of degradation by nucleases during delivery and improves its cellular uptake and cytoplasmic delivery efficiency. After miR-210@ZIF-8 is taken up by cardiomyocytes, ZIF-8 dissociates in an acidic endosome or lysosomal environment, thereby promoting the release of miR-210.
[0068] Specifically, in this embodiment, the preparation of the above-mentioned methacrylamide hyaluronic acid... S1A-1: Weigh 1.0g of sodium hyaluronate, add it to 100mL of deionized water, and stir overnight at 4℃ until the hyaluronic acid is completely dissolved to obtain a hyaluronic acid solution with a mass-volume concentration of 1%.
[0069] S1A-2: The hyaluronic acid solution was placed in an ice bath and stirred continuously. The pH of the reaction solution was adjusted to 8.0–9.0 using sodium hydroxide solution. Then, 0.74 mL of methacrylic anhydride was slowly added dropwise over 2 hours, with the pH continuously monitored during the addition. The pH was maintained at 8.0–9.0 by adding 0.5 mol / L sodium hydroxide solution. After the addition was complete, the reaction was continued at 4°C for 24 hours to allow the hydroxyl groups on the hyaluronic acid molecular chain to undergo an esterification reaction with methacrylic anhydride, producing a methacryloyl-containing reaction solution with photocrosslinkable methacryloyl groups.
[0070] S1A-3: After the reaction is complete, add 2.92 g of sodium chloride to the reaction solution to achieve a final sodium chloride concentration of 0.5 mol / L, in order to terminate the reaction and promote subsequent precipitation of the product. Slowly add the reaction solution to 5 times its volume of pre-cooled anhydrous ethanol, stir thoroughly, and let stand for 30 min to allow methacrylamide hyaluronic acid to precipitate. Collect the precipitate by centrifugation at 5000×g for 5 min, and wash twice with pre-cooled anhydrous ethanol to obtain the preliminary precipitate of acid.
[0071] S1A-4: The obtained preliminary precipitated acid was redissolved in deionized water and placed in a dialysis bag with a molecular weight cutoff of 3500–8000 Da. Dialysis was performed in deionized water for 4 days, with the dialysate changed every 8–12 hours to remove unreacted methacrylic anhydride, methacrylic acid, and other small molecule impurities. After dialysis, the solution was pre-frozen at -80°C and then freeze-dried to obtain white, spongy methacryloyl hyaluronic acid.
[0072] S1A-5, methacrylamide hyaluronic acid, is sealed and stored at -20°C for later use.
[0073] Preparation of oxidized dextran S1B-1: Weigh 10.0g of dextran and add it to 100mL of deionized water. Stir continuously at room temperature until completely dissolved. Separately, weigh 5.0g of sodium periodate and dissolve it in 50mL of deionized water.
[0074] S1B-2, under light-protected conditions, sodium periodate solution was slowly added dropwise to dextran solution, and the reaction was stirred at room temperature for 4 hours. During the reaction, sodium periodate caused the ortho-dihydroxyl group in the dextran sugar ring structure to undergo oxidative cleavage, forming aldehyde groups on the dextran molecular chain, and obtaining a preliminary aldehyde group reaction solution. In S1B-3, the initial aldehyde reaction solution after the reaction was completed was added to 10 mL of ethylene glycol, and stirring was continued for 1 hour to consume unreacted sodium periodate and terminate the oxidation reaction, obtaining an initial solution containing oxidized dextran powder. This initial solution was placed in a dialysis bag with a molecular weight cutoff of 3500–8000 Da and dialyzed in deionized water in the dark for 3 days, changing the dialysate 4 times daily. After dialysis, the solution was pre-frozen at -80°C and freeze-dried to obtain oxidized dextran powder. The purpose of dialysis is to remove sodium periodate, iodate, ethylene glycol, and other small molecule reaction products.
[0075] S1B-4, store the oxidized dextran powder in a sealed container away from light.
[0076] The preparation of miR-210@ZIF-8 nanoparticles is specifically described in this embodiment: S1C-1, all water, centrifuge tubes, and pipette tips that come into contact with miR-210 are made of nuclease-free materials. 40 mmol / L zinc acetate solution and 1.28 mol / L 2-methylimidazole solution were prepared using water treated with diethyl pyrocarbonate.
[0077] For S1C-2, take 1.0 mL of 40 mmol / L zinc acetate solution, add 100 μL of 20 μmol / L miR-210 solution, gently mix, and incubate at room temperature for 10 min to allow Zn to... 2+ It interacts electrostatically with the negatively charged phosphate backbone of miR-210 and forms a mixture of nucleation sites.
[0078] S1C-3, under rapid stirring, 1.0 mL of a 1.28 mol / L 2-methylimidazole solution was quickly added to the above mixture. The molar ratio of zinc acetate to 2-methylimidazole was 1:32. After the addition of 2-methylimidazole, the reaction solution became turbid, indicating that the ZIF-8 coordination structure began to form. The reaction solution was allowed to stand at room temperature for 20 min to form a preliminary coated nanofluid that simultaneously encapsulates miR-210 during the ZIF-8 formation process.
[0079] After the reaction of S1C-4, the initially loaded nanofluid was centrifuged at 12000 rpm for 15 min, the supernatant was discarded, and the precipitate was resuspended in water treated with diethyl pyrocarbonate and washed three times to remove free miR-210, unreacted zinc ions, and 2-methylimidazole. The obtained miR-210@ZIF-8 could be resuspended to 5 mg / mL for subsequent hydrogel loading; alternatively, it could be freeze-dried and stored at -20°C in the dark.
[0080] The obtained miR-210@ZIF-8 nanoparticles were characterized by scanning electron microscopy, transmission electron microscopy, particle size analysis, and zeta potential analysis. The miR-210 loaded particles still maintained a polyhedral structure, with the main particle size distribution being 140–220 nm, and the surface potential changed from approximately +20 mV to approximately -13 mV.
[0081] Methacrylamide hyaluronic acid, oxidized dextran, and miR-210@ZIF-8 nanoparticles were prepared by using deionized water to prepare 5% w / v methacrylamide hyaluronic acid solutions and 10% w / v oxidized dextran solutions, respectively.
[0082] In specific step S2, the preparation of the hydrogel bio-ink loaded with miR-210@ZIF-8 is specifically described in this embodiment: 1) Add miR-210@ZIF-8 nanoparticles to a solution of methacryloyl hyaluronic acid, and disperse the nanoparticles uniformly by gentle blowing or low-speed vortexing. The final concentration of the miR-210@ZIF-8 nanoparticles in the hydrogel bio-ink is 0.1–1.0 mg / mL, preferably 0.5 mg / mL.
[0083] 2) Then add the gelatin solution and mix evenly at 37°C. Then add the photoinitiator solution and stir in the dark. Finally, add the oxidized dextran solution with an oxidation degree of 20% and mix quickly to obtain the hydrogel bio-ink loaded with miR-210@ZIF-8.
[0084] 3) Taking the preparation of 1 mL of hydrogel bio-ink as an example, take 500 μL of 5% w / v methacrylamide hyaluronic acid solution, add 0.5 mg miR-210@ZIF-8 nanoparticles and disperse them fully; then add 300 μL of 10% w / v gelatin solution and mix evenly at 37℃; then add 100 μL of 2.5% w / v photoinitiator solution and mix in the dark; finally add 100 μL of 10% w / v oxidized dextran solution with an oxidation degree of 20% and mix quickly.
[0085] 4) In the obtained hydrogel bio-ink, the final concentration of methacrylamide hyaluronic acid was 2.5% w / v, the final concentration of gelatin was 3.0% w / v, the final concentration of oxidized dextran ODEX with an oxidation degree of 20% was 1.0% w / v, the final concentration of photoinitiator was 0.25% w / v, and the final concentration of miR-210@ZIF-8 nanoparticles was 0.5 mg / mL.
[0086] 5) miR-210@ZIF-8 nanoparticles are preferentially dispersed in a methacrylamide hyaluronic acid solution, followed by the sequential addition of gelatin solution, photoinitiator LAP, and oxidized dextran ODEX. This order of addition avoids the premature formation of a dynamic Schiff base crosslinking network between oxidized dextran and gelatin, which would otherwise increase the viscosity of the system and is beneficial for the uniform distribution of miR-210@ZIF-8 in the hydrogel bio-ink.
[0087] 6) When miR-210@ZIF-8 nanoparticles are added in the form of an aqueous dispersion, a high-concentration nanoparticle dispersion should be used, and the amount of deionized water added in the formulation should be reduced accordingly to maintain the final concentration and total volume of each component of the hydrogel. Freshly prepared miR-210@ZIF-8 dispersion is preferred to avoid repeated freeze-thaw cycles that could cause nanoparticle aggregation or miR-210 degradation.
[0088] 7) For sterility testing, methacrylamide hyaluronic acid, gelatin, oxidized dextran, photoinitiator, and deionized water were sterilized separately before mixing. miR-210@ZIF-8 nanoparticles were prepared, centrifuged, and washed under nuclease-free and sterile conditions. The intact bio-ink loaded with miR-210@ZIF-8 nanoparticles was no longer filtered through a 0.22 μm filter to avoid nanoparticle retention.
[0089] In step S3 of this embodiment, the DLP3D printing of the heart patch specifically involves: 1) Establish a 3D model based on the target shape and size of the cardiac patch. The cardiac patch is designed as a regular mesh structure with a planar size of 10mm × 10mm, a target thickness of approximately 2mm, and a mesh aperture size of 1mm.
[0090] 2) Import the 3D model into the slicing software and perform layer-by-layer slicing. Place the DLP printer in a bio-clean workbench and sterilize the printing platform, ink tank, and work area before printing. Add sterile hydrogel bio-ink loaded with miR-210@ZIF-8 nanoparticles to the printing ink tank, avoiding the formation of obvious air bubbles, and start the printing program to perform layer-by-layer photocuring.
[0091] 3) Specific printing parameters: Printing uses a 405nm light source, a layer thickness of 0.05mm, 35 layers, a curing time of 20s per layer, a resting time of 3s between layers, and a bottom layer of 3 layers. Under these conditions, the theoretical printing thickness corresponding to 35 layers is 1.75mm, and the target thickness of the formed patch is approximately 2mm. The printing parameters used are consistent with existing printing records.
[0092] 4) During the printing process, the photoinitiator in the hydrogel bio-ink initiates the polymerization of methacryloyl groups on the methacryloyl hyaluronic acid molecular chain under 405nm light irradiation, so that each printed layer forms a stable photocrosslinking network; at the same time, the dynamic Schiff base network formed between the oxidized dextran with an oxidation degree of 20% and gelatin is retained in the printed structure, so that the resulting patch has both printing stability and stress relaxation performance.
[0093] 5) After printing, gently remove the hydrogel patch from the printing platform and wash it three times with sterile deionized water for 5 minutes each time to remove uncrosslinked hydrogel components, free photoinitiators and unembedded nanoparticles on the surface.
[0094] 6) The resulting cardiac patch has a regular grid structure and interconnected pores, providing channels for the transport of oxygen, nutrients, and metabolic products. After printing, the patch is placed in sterile deionized water and stored for a short period at 4°C. When used for cell or animal experiments, it is preferable to use it immediately after preparation.
[0095] It should be noted that the methacrylamide hyaluronic acid solution, gelatin solution, dextran solutions with different oxidation degrees, and photoinitiator solution are used to construct a stress relaxation hydrogel system.
[0096] Compared with the control group: The concentrations of the methacryloyl hyaluronic acid solution were 5% w / v, the gelatin solution was 10% w / v, the dextran or oxidized dextran solution was 10% w / v, and the photoinitiator solution was 2.5% w / v. The oxidation degrees of the dextran solutions were 0%, 10%, and 20%, with the 0% group using unoxidized dextran.
[0097] It should be noted that the oxidation degree of the dextran solution is controlled by adjusting the amount of sodium periodate added.
[0098] Sodium periodate (NaIO4) selectively cleaves the carbon-carbon bonds between adjacent hydroxyl groups at C2–C3 (and C3–C4) of glucose units, resulting in the formation of two aldehyde groups (dialdehyde units) for each oxidized glucose unit. Therefore: Oxidation degree 10% ≈ Approximately 10 out of every 100 glucose units are oxidized → Approximately 20 aldehyde groups Oxidation degree 20% ≈ Approximately 20 units out of every 100 units are oxidized → Approximately 40 aldehyde groups ② Preparation (controlled by the ratio of NaIO4 to dextran (based on the molar number of glucose units): oxidizing one glucose unit consumes 1 mole of NaIO4, so the theoretical degree of oxidation ≈ molar number of NaIO4 ÷ molar number of glucose units. Adding 10% equivalent of NaIO4 → theoretical 10% oxidation; adding 20% equivalent → theoretical 20% oxidation.
[0099] 2) To prepare 1 mL of hydrogel precursor solution, 500 μL of methacrylamide hyaluronic acid solution and 300 μL of gelatin solution were mixed thoroughly at 37 ℃. Then, 100 μL of photoinitiator solution was added and mixed in the dark. Finally, 100 μL of dextran solution with oxidation degrees of 0%, 10%, or 20% were added to obtain hydrogel precursor solutions HGO-0, HGO-10, and HGO-20, respectively. The final concentrations of methacrylamide hyaluronic acid, gelatin, dextran solution, and photoinitiator in each group were 2.5% w / v, 3.0% w / v, 1.0% w / v, and 0.25% w / v, respectively.
[0100] 3) The obtained precursor solution was incubated at 37 °C for 5 min, followed by photocuring under 405 nm light for 30 s. In the system containing oxidized dextran, the aldehyde groups of oxidized dextran and the amino groups of gelatin form reversible Schiff base crosslinks, while methacrylamide hyaluronic acid forms a stable crosslinking network through photopolymerization, thereby constructing a composite hydrogel composed of a stable photocrosslinking network and a dynamic crosslinking network.
[0101] 4) Each group maintained the same final concentration of components, total solid content, and photocuring conditions, only changing the degree of oxidation of the dextran solution to regulate the degree of dynamic crosslinking and the stress relaxation behavior of the hydrogel.
[0102] 5) The storage modulus, loss modulus, and stress relaxation properties of each group of hydrogels were evaluated using a rotational rheometer. Furthermore, Drp1 expression and mitochondrial morphology in cardiomyocytes under different hydrogel conditions were detected. The results showed that, under conditions of similar initial mechanical properties, hydrogel HGO-20 exhibited faster stress relaxation characteristics and could more significantly reduce Drp1 expression and mitochondrial fragmentation. Therefore, hydrogel HGO-20 was selected as the base hydrogel formulation for subsequent miR-210@ZIF-8 loading and cardiac patch preparation.
[0103] 4.6 Preparation of hydrogel bio-ink loaded with miR-210@ZIF-8 is specifically described in this embodiment: 1) The hydrogel HGO-20 obtained from screening in section 4.5 was used as the base hydrogel system. miR-210@ZIF-8 nanoparticles were added to a solution of methacrylamide hyaluronic acid and dispersed thoroughly by gentle blowing or low-speed vortexing. The final concentration of miR-210@ZIF-8 in the hydrogel bio-ink was 0.1-1.0 mg / mL, preferably 0.5 mg / mL.
[0104] 2) Then add the gelatin solution and mix evenly at 37 °C. Then add the photoinitiator solution and mix in the dark. Finally, add the oxidized dextran solution with an oxidation degree of 20% and mix quickly to obtain the hydrogel bio-ink loaded with miR-210@ZIF-8.
[0105] 3) Taking the preparation of 1 mL hydrogel bio-ink as an example, take 500 μL of 5% w / v methacrylamide hyaluronic acid solution, add 0.5 mg miR-210@ZIF-8 nanoparticles and disperse them fully; then add 300 μL of 10% w / v gelatin solution and mix evenly at 37 ℃; then add 100 μL of 2.5% w / v photoinitiator solution and mix in the dark; finally add 100 μL of 10% w / v oxidized dextran solution with an oxidation degree of 20% and mix quickly.
[0106] 4) In the obtained hydrogel bio-ink, the final concentration of methacrylamide hyaluronic acid was 2.5% w / v, the final concentration of gelatin was 3.0% w / v, the final concentration of oxidized dextran with an oxidation degree of 20% was 1.0% w / v, the final concentration of photoinitiator was 0.25% w / v, and the final concentration of miR-210@ZIF-8 was 0.5 mg / mL.
[0107] 5) miR-210@ZIF-8 nanoparticles are preferentially dispersed in a methacrylamide hyaluronic acid solution, followed by the sequential addition of gelatin, photoinitiator, and oxidized dextran. This reduces the increased viscosity of the system caused by premature dynamic cross-linking between oxidized dextran and gelatin, thus promoting the uniform distribution of nanoparticles in the bio-ink. The entire process is conducted in the dark after the addition of the photoinitiator.
[0108] 6) When used in cell or in vivo experiments, each hydrogel component is sterilized before mixing. miR-210@ZIF-8 is prepared and washed under sterile, nuclease-free conditions. The intact bio-ink loaded with miR-210@ZIF-8 is no longer filtered through a 0.22 μm filter membrane to avoid retention of miR-210@ZIF-8 nanoparticles. The resulting bio-ink is prepared and used immediately.
[0109] 5. Experimental Results 5.1 Abnormal biomechanical microenvironment after myocardial infarction promotes Drp1 expression in cardiomyocytes Figure 1 A in Figure 1 B in the figures represent gross morphological images of the myocardium of rats in the Sham group (sham-operated group) and the MI group (myocardial infarction group), respectively. Figure 1 C in Figure 1 The D in the figure represents a statistical comparison of Young's modulus and stress relaxation time between normal myocardium and infarcted myocardium. Figure 1 E in the figure represents the Western blot results of Col1A1 (type I collagen α1 chain) and α-SMA (α-smooth muscle actin), markers of myocardial fibrosis. Figure 1 F in the diagram represents a basal cell culture model of PDMS (polydimethylsiloxane) with different stiffnesses; Figure 1 G in the figure represents a statistical comparison of Young's modulus for different soft and hard PDMS substrates; Figure 1 H in Figure 1 The figure I in the image shows the results of detecting the mRNA and protein expression levels of Drp1 (dynein-associated protein 1) in cardiomyocytes on substrates of different stiffness. Western blot is a protein immunoblotting technique.
[0110] like Figure 1 A in Figure 1 As shown in B in the figure. To evaluate the changes in the myocardial tissue biomechanical microenvironment after myocardial infarction, a rat model of myocardial infarction was first established. Gross observation of the heart showed that, compared with the Sham group, the MI group had obvious pale scar formation in the infarct area, suggesting significant tissue remodeling after myocardial infarction.
[0111] like Figure 1 C in Figure 1As shown in D in the figure. Further mechanical properties of myocardial tissue were examined. The results showed that, compared with the Sham group, the Young's modulus of myocardial tissue in the MI group was significantly increased, while the stress relaxation time was significantly prolonged, indicating that myocardial tissue not only undergoes matrix hardening after myocardial infarction, but also its stress dissipation capacity under continuous deformation conditions decreases.
[0112] Western blot analysis showed that the expression of fibrosis-related proteins Col1A1 (type I collagen α1 chain) and α-SMA (α-smooth muscle actin) was significantly increased in the myocardial tissue of the MI group, further indicating that myocardial infarction is accompanied by increased collagen deposition and fibrotic remodeling. Figure 1 (E in the text). To further evaluate the effect of changes in matrix mechanical properties on Drp1 expression in cardiomyocytes, PDMS substrates with substrate-to-curing agent ratios of 20:1 and 10:1 were used to simulate relatively soft and relatively hard extracellular mechanical environments, respectively, and fibronectin was coated on the PDMS surface. Figure 1 The mechanical testing results showed that the Young's modulus of the 10:1 PDMS substrate was significantly higher than that of the 20:1 PDMS substrate, indicating that cell culture substrates with different stiffnesses were successfully constructed. Figure 1 (G in the text). After culturing cardiomyocytes on PDMS substrates of different stiffnesses, RT-qPCR (real-time quantitative PCR) showed that, compared with the 20:1 soft substrate, the expression of Drp1 mRNA in cardiomyocytes on the 10:1 hard substrate was significantly increased; Western blot analysis further showed that the expression of Drp1 protein in the hard substrate group was also significantly increased. Figure 1 H in Figure 1 (I in the middle). Figure 3 This demonstrates that the present embodiment can stably print the target porous support structure.
[0113] The above results indicate that myocardial tissue undergoes both matrix stiffening and decreased stress relaxation capacity after myocardial infarction, accompanied by an increase in fibrosis. Meanwhile, higher matrix stiffness can promote Drp1 expression in cardiomyocytes, suggesting that the abnormal mechanical microenvironment after myocardial infarction may be involved in the regulation of Drp1-related mitochondrial division, providing experimental evidence for further use of stress relaxation hydrogels to improve abnormal mechanical stimulation.
[0114] Stress-relaxed hydrogels inhibit excessive mitochondrial division in cardiomyocytes.
[0115] To evaluate the effect of hydrogel stress relaxation properties on mitochondrial division in cardiomyocytes, HGO-0, HGO-10, and HGO-20 hydrogels were constructed by adjusting the oxidation degree of oxidized dextran. Figure 2 (A) Fourier transform infrared spectroscopy results further support the formation of the composite hydrogel network ( Figure 2 (C in the middle). Figure 2 A in Figure 2 The B in the figure directly reflects that, compared to the low oxidation degree system, the stress relaxation performance is significantly improved, and the ability to regulate the mechanical microenvironment is greatly enhanced. HGO (methacrylamide hyaluronic acid-gelatin-oxidized dextran composite hydrogel); HGO-0 (HGO hydrogel with 0% dextran oxidation); HGO-10 (HGO hydrogel with 10% dextran oxidation); HGO-20 (HGO hydrogel with 20% dextran oxidation).
[0116] Rheological analysis showed that HGO-0, HGO-10, and HGO-20 hydrogels had similar initial elastic moduli, but their stress relaxation times differed significantly. With increasing oxidation degree of oxidized dextran, the stress relaxation rate of the hydrogels gradually increased, with the HGO-20 group exhibiting the fastest stress relaxation behavior. Figure 2 (D in the middle).
[0117] Cardiomyocytes were cultured on hydrogels with different stress relaxation properties. The results showed that as the stress relaxation rate of the hydrogel increased, the expression of Drp1 mRNA in cardiomyocytes gradually decreased, with the lowest Drp1 expression observed in the HGO-20 group. Figure 2 E in the text). Further Western blot analysis of Drp1 protein expression revealed results consistent with changes in transcriptional levels; the HGO-20 group showed the lowest Drp1 protein expression (…). Figure 2 (F in the text). Subsequently, mitochondrial fluorescence staining was used to observe the morphological changes of cardiomyocytes under different stress relaxation microenvironments. The mitochondria in the HGO-0 group showed significant fragmentation, while as the hydrogel stress relaxation rate increased, the mitochondria gradually elongated and formed a more continuous network structure. The HGO-20 group exhibited the best mitochondrial morphological integrity. Figure 2 (G in the text). Quantitative analysis of mitochondrial morphological parameters further confirmed that the degree of mitochondrial fragmentation was significantly reduced in the HGO-20 group, and the mitochondrial network structure was significantly improved. Figure 2 The results above indicate that, under conditions of similar initial stiffness, accelerating hydrogel stress relaxation can reduce Drp1 expression in cardiomyocytes and decrease mitochondrial fragmentation, thereby inhibiting excessive mitochondrial division associated with abnormal mechanical stimulation.
[0118] DLP Printing and Structural Characterization of Stress-Relaxed Hydrogel Cardiac Patch To evaluate the DLP printing performance of stress-relaxed hydrogels, a regular mesh-like hydrogel heart patch was fabricated using DLP 3D printing technology. During the printing process, hydrogel bio-ink was added to the printing chamber, and the patch was formed through layer-by-layer photocuring. The layer thickness was set to 0.05 mm, the planar dimensions were 10 mm × 10 mm, the target thickness was approximately 2 mm, the number of layers was 35, the photocuring time for each layer was 20 s, the interlayer settling time was 3 s, and the bottom layer consisted of 3 layers. Figure 3 (A in the middle).
[0119] The printing results show that the hydrogel can be continuously molded layer by layer under the above conditions, resulting in a complete overall structure of the patch that maintains the preset regular grid morphology well. After coloring, the regularly distributed macroscopic pores inside the patch can be clearly observed, with a designed pore diameter of approximately 1 mm, forming an interconnected grid structure. Figure 3 B in Figure 3 (C in the text). This structure provides a pathway for the transport and exchange of oxygen, nutrients, and metabolites within the patch.
[0120] Further scanning electron microscopy was used to observe the internal microstructure of the hydrogel patch. The results showed that the patch exhibited a highly porous three-dimensional network structure, with pores mainly appearing as irregular polygons, relatively uniformly distributed, and most micropores having a diameter of approximately 100 μm. The pore walls were thin and the surface was relatively smooth, with good connectivity between the pores. Figure 3 (D in the middle).
[0121] The above results demonstrate that stress-relaxed hydrogels possess excellent DLP printing capabilities, enabling the construction of hydrogel cardiac patches with regular macroscopic meshes and interconnected microscopic pores, providing a structural basis for subsequent miR-210@ZIF-8 loading and myocardial repair applications.
[0122] Preparation, characterization and intracellular delivery of miR-210@ZIF-8 To improve the stability and intracellular delivery efficiency of miR-210, miR-210@ZIF-8 nanoparticles were prepared using a one-step co-precipitation method. miR-210 was then mixed with Zn... 2+ Premixed, followed by the addition of 2-methylimidazole, ZIF-8 is formed through coordination self-assembly, and miR-210 is simultaneously loaded during particle formation. Figure 4 (A) Scanning electron microscopy and transmission electron microscopy showed that both ZIF-8 and miR-210@ZIF-8 exhibited relatively uniform polyhedral structures. The miR-210 particles, after loading, retained the basic morphology of ZIF-8, with no obvious structural damage observed. Figure 4 (B in the middle).
[0123] Zeta potential detection showed that the surface potential of blank ZIF-8 was approximately +20 mV, while after loading miR-210, the surface potential of miR-210@ZIF-8 changed to approximately -13 mV, showing a significant charge reversal, which supports the successful loading of negatively charged miR-210 into ZIF-8 nanoparticles. Figure 4 (C in the text). Particle size analysis results show that the particle sizes of ZIF-8 and miR-210@ZIF-8 are mainly distributed in the range of 140–220 nm. The particle size increases slightly after loading with miR-210, but the overall distribution remains relatively concentrated. Figure 4 (D in the middle).
[0124] To further evaluate the intracellular delivery capability of miR-210@ZIF-8, the distribution of fluorescently labeled miR-210 in cardiomyocytes was observed. After 4 h of culture, the fluorescence of miR-210 and lysosomal cells showed a high degree of overlap, with a colocalization coefficient of approximately 0.92, indicating that miR-210@ZIF-8 was mainly localized in lysosomes after being taken up by cells. After the culture time was extended to 24 h, the colocalization coefficient decreased to approximately 0.57, while the fluorescence of miR-210 in the cytoplasmic region significantly increased, indicating that miR-210@ZIF-8 can achieve time-dependent endosome / lysosomal escape and promote the release of miR-210 into the cytoplasm. Figure 4 (E in the text).
[0125] The above results indicate that miR-210 can be successfully loaded into ZIF-8 nanoparticles, and the resulting miR-210@ZIF-8 has good cellular uptake and intracellular delivery capabilities, which can promote the transfer of miR-210 from the endosome / lysosome compartment to the cytoplasm, providing a basis for its further biological regulatory role.
[0126] miR-210@ZIF-8 improves mitochondrial function in hypoxic cardiomyocytes To evaluate the protective effect of miR-210@ZIF-8 on hypoxic-damaged cardiomyocytes, an oxygen-glucose deprivation (OGD) model was established, and normal control group, OGD group, free miR-210 group and miR-210@ZIF-8 group were set up.
[0127] JC-1 staining was used to evaluate the mitochondrial membrane potential of cardiomyocytes under different treatment conditions. The results showed that the normal control group exhibited predominantly red aggregated fluorescence, while OGD (oxygen-glucose deprivation) treatment significantly reduced red fluorescence and enhanced green monomeric fluorescence, indicating that hypoxic damage led to a significant decrease in mitochondrial membrane potential. Treatment with free miR-210 somewhat improved these changes, while the green fluorescence in the miR-210@ZIF-8 group further decreased, suggesting that miR-210@ZIF-8 can more effectively maintain the mitochondrial membrane potential of hypoxic cardiomyocytes. Figure 5 A in Figure 5 (C in the middle).
[0128] EdU (5-ethynyl-2′-deoxyuridine) staining was further used to evaluate the proliferative status of cardiomyocytes. The results showed that the number of EdU-positive cells significantly decreased after OGD (oxygen-glucose deprivation) treatment, suggesting that hypoxic injury inhibited cardiomyocyte proliferation; after treatment with free miR-210 and miR-210@ZIF-8, the number of EdU-positive cells increased, with the miR-210@ZIF-8 group showing more significant improvement. Figure 5 (B in the middle).
[0129] ATP detection results showed that the intracellular ATP level of cardiomyocytes decreased significantly after OGD treatment, indicating that hypoxic injury led to impaired cellular energy metabolism; after treatment with free miR-210 and miR-210@ZIF-8, the ATP level was restored to some extent, with the miR-210@ZIF-8 group showing more significant recovery. Figure 5 (D in the middle).
[0130] The above results indicate that miR-210@ZIF-8 can alleviate the OGD-induced decrease in mitochondrial membrane potential, improve the energy metabolism of cardiomyocytes under hypoxic conditions, and promote cell proliferation, thereby playing a protective role against hypoxic-damaged cardiomyocytes.
[0131] Composite hydrogel cardiac patches reduce myocardial damage and fibrosis after myocardial infarction. To evaluate the effect of stress-relaxation hydrogel loaded with miR-210@ZIF-8 nanoparticles on tissue repair after myocardial infarction, a rat myocardial infarction model was established, and normal control group, MI group, HGO hydrogel group and HGO@miR-210@ZIF-8 group were set up.
[0132] H&E (hematoxylin-eosin) staining results showed that the normal control group had intact myocardial tissue structure, with dense and regular arrangement of myocardial fibers; the MI group showed obvious thinning of the ventricular wall, disordered arrangement of myocardial fibers, and a large amount of scar tissue replacement. After treatment with HGO stress relaxation hydrogel, the myocardial tissue structure in the infarcted area was improved to some extent, and the integrity of the ventricular wall was restored; after further loading with miR-210@ZIF-8, the ventricular wall structure and myocardial tissue arrangement in the HGO@miR-210@ZIF-8 group were further improved compared with the HGO group, and the residual myocardial tissue was significantly increased. Figure 6 (A in the middle).
[0133] Masson staining results showed that the infarct area of the MI group had a large area of blue-stained collagen tissue, indicating significant collagen deposition and fibrotic remodeling after myocardial infarction. HGO hydrogel treatment reduced collagen deposition, but a significant amount of fibrous tissue remained in the infarct area; the HGO@miR-210@ZIF-8 group showed further reduction in collagen deposition while retaining more myocardial tissue, exhibiting a more significant anti-fibrotic effect. Figure 6 (B in the middle).
[0134] The above results indicate that stress-relaxation hydrogels can alleviate tissue damage and fibrotic remodeling after myocardial infarction to a certain extent. On this basis, loading miR-210@ZIF-8 further enhances its protective effect on infarcted myocardial structures, suggesting that stress-relaxation mechanical regulation and miR-210-mediated cardiomyocyte protection can synergistically promote tissue repair after myocardial infarction.
[0135] The key advantage of this invention lies in its construction of a stress-relaxation hydrogel using a photocrosslinking network of methacryloyl hyaluronic acid and a dynamic Schiff base network of oxidized dextran-gelatin. Furthermore, the degree of dynamic crosslinking and stress relaxation behavior are controlled by adjusting the oxidation level of oxidized dextran. While maintaining a relatively consistent initial material stiffness, the material can reduce the continuous abnormal mechanical stimulation experienced by cardiomyocytes through faster stress dissipation, thereby reducing Drp1 expression and mitochondrial fragmentation. This demonstrates a mechanical control advantage distinct from traditional static support materials.
[0136] On the other hand, this invention uses ZIF-8 loaded with miR-210, which improves the stability, cellular uptake efficiency, and intracellular delivery capacity of miR-210. Furthermore, the responsive dissociation of ZIF-8 in an acidic intracellular environment promotes miR-210 release, thereby improving the mitochondrial membrane potential and energy metabolism of cardiomyocytes under hypoxic conditions, demonstrating a metabolic regulatory advantage against hypoxic injury after myocardial infarction. Simultaneously, this invention further prepares the above system into a hydrogel bio-ink suitable for DLP 3D printing, capable of forming cardiac patches with a regular grid and interconnected microporous structures. Therefore, this invention can synergistically exert its effects on both the relief of abnormal mechanical stimulation and the protection of mitochondrial function / energy metabolism, offering more comprehensive myocardial protection and anti-fibrotic repair advantages compared to existing materials that only provide mechanical support or single drug delivery.
[0137] The hydrogel cardiac patch is constructed with a dual cross-linked structure combining a photocrosslinked stable network of methacryloyl hyaluronic acid and a dynamic Schiff base cross-linked network of oxidized dextran-gelatin. The static photocrosslinked network ensures the overall structural and mechanical stability of the patch, while the dynamic Schiff base cross-linked network endows the hydrogel with higher stress relaxation efficiency and stress dissipation capacity, which can effectively relieve the abnormal hardening mechanical stress in the myocardial infarction lesion area and reshape the benign myocardial mechanical microenvironment. At the same time, the higher nanoparticle loading can provide a sufficient and continuous supply of miR-210 drugs for myocardial tissue repair.
[0138] The cardiac patch of this application can improve myocardial energy metabolism disorders after myocardial infarction, slightly inhibit abnormal collagen deposition in the myocardium, and reduce local pathological fibrotic remodeling. The hydrogel cardiac patch is constructed with a dual cross-linked structure combining a photocrosslinked stable network of methacryloyl hyaluronic acid and a dynamic Schiff base cross-linked network of oxidized dextran-gelatin. The static photocrosslinked network ensures the overall structural and mechanical stability of the patch, while the dynamic Schiff base cross-linked network endows the hydrogel with higher stress relaxation efficiency and stress dissipation capacity, which can effectively dissipate the abnormal hardening mechanical stress in the myocardial infarction lesion area and reshape a benign myocardial mechanical microenvironment. At the same time, the higher nanoparticle loading can provide a sufficient and continuous supply of miR-210 drug for myocardial tissue repair.
[0139] By optimizing the proportions of each group, the optimal balance between the static photocrosslinking network and the dynamic Schiff base crosslinking network is achieved. The 20% high oxidation degree endows the hydrogel with excellent and controllable stress relaxation properties, which can precisely dissipate abnormal mechanical stimulation after myocardial infarction and inhibit the pathological process of mitochondrial fragmentation mediated by Drp1 from the source. The appropriate photocrosslinking density ensures the structural stability and mechanical compatibility of the patch after long-term implantation. The nanoparticle loading can achieve long-term and stable acid-response drug release, avoiding the problems of drug overload or underload.
[0140] Example 3 An application of a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8, characterized by utilizing the technical content described in Examples 2-3 above, specifically the method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8, as described in Example 1 above, for application in myocardial repair after myocardial infarction, to inhibit excessive mitochondrial division in cardiomyocytes, alleviate hypoxia-related mitochondrial dysfunction and myocardial fibrosis remodeling, and promote the repair of infarcted myocardial tissue.
[0141] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other modifications under the guidance of the present invention without departing from the spirit and scope of the claims. All of these modifications are within the scope of protection of the present invention.
Claims
1. A stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8, characterized in that: The bio-ink is formed by 3D printing of a hydrogel bio-ink, which includes a composite hydrogel matrix and miR-210@ZIF-8 nanoparticles, wherein the miR-210@ZIF-8 nanoparticles are uniformly distributed within the composite hydrogel matrix.
2. The stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8 according to claim 1, characterized in that: The composite hydrogel matrix is configured as a double cross-linked network structure composite hydrogel matrix. The dual cross-linked network structure composite hydrogel matrix includes a cross-linking stable network and a dynamic cross-linking network. The cross-linking stable network is formed by photocrosslinkable polymer polymerization to maintain the overall structural and dimensional stability of the cardiac patch. The dynamic cross-linking network is constructed by aldehyde-containing polysaccharides and amino-containing proteins through dynamic Schiff base bonds.
3. The stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8 according to claim 2, characterized in that: The photocrosslinkable polymer is methacrylamide hyaluronic acid, the aldehyde-containing polysaccharide is oxidized dextran, and the amino-containing protein is gelatin; the miR-210@ZIF-8 nanoparticles are uniformly distributed in the methacrylamide hyaluronic acid. The composite hydrogel matrix also contains the photoinitiator LAP.
4. The stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8 according to claim 3, characterized in that, The miR-210@ZIF-8 nanoparticles are provided with miR-210 and ZIF-8 nanoparticles, with miR-210 coating the ZIF-8 nanoparticles; the ZIF-8 nanoparticles are uniformly distributed in the methacrylamide hyaluronic acid.
5. A method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8, characterized in that, Prepare a stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8 as described in any one of claims 1-4.
6. The method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8 according to claim 5, characterized in that, Includes the following steps: S1. Methacrylamide hyaluronic acid, oxidized dextran, and miR-210@ZIF-8 nanoparticles were prepared separately, and deionized water was used to prepare 5% w / v methacrylamide hyaluronic acid solution and 10% w / v oxidized dextran solution, respectively. S2. Preparation of sterile printable hydrogel bio-ink: Using a step-by-step feeding process, the miR-210@ZIF-8 nanoparticles are uniformly dispersed in the methacryloyl hyaluronic acid solution to obtain pre-dissolved solution 1; under constant temperature T1, gelatin solution is added to the pre-dissolved solution 1 and mixed to obtain pre-dissolved solution 2; under light-protected conditions, photoinitiator solution is added to the pre-dissolved solution 2 and stirred to obtain pre-dissolved solution 3; finally, the oxidized dextran solution is rapidly added to the pre-dissolved solution 3 and mixed to obtain the hydrogel bio-ink; S3. Digital light processing 3D printing molding: The hydrogel bio-ink is stereolithographically cured and 3D printed using a digital light processing 3D printing device. After molding, it is washed with sterile deionized water to remove uncrosslinked impurities, thus obtaining the stress-relaxed hydrogel heart patch.
7. The method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8 according to claim 6, characterized in that, The specific preparation method of methacrylamide hyaluronic acid in step S1 is as follows: S1A-1, dissolve sodium hyaluronate in deionized water to prepare a hyaluronic acid solution with a mass-volume concentration of 1%; S1A-2, after adjusting the pH value to pH 8.0-9.0 by stirring the hyaluronic acid solution in an ice bath, methacrylic anhydride is added dropwise within the reaction time S. After the addition is completed, the reaction is continued at 4°C for 24 hours to allow the hydroxyl groups on the hyaluronic acid molecular chain to undergo an esterification reaction with methacrylic anhydride to produce a photocrosslinkable methacryloyl reaction solution. S1A-3, the methacrylamide reaction solution is added to sodium chloride to make the final concentration of sodium chloride reach 0.5 mol / L, and then the reaction is terminated to obtain a terminated reaction mixed solution; The termination reaction mixture was slowly added to 5 times the volume of pre-cooled anhydrous ethanol, stirred thoroughly, and allowed to stand for 30 minutes to allow methacrylamide hyaluronic acid to precipitate. The precipitate was collected by centrifugation at 5000×g for 5 minutes and washed twice with pre-cooled anhydrous ethanol to obtain the preliminary precipitate acid. S1A-4, the preliminary precipitated acid is redissolved in deionized water and dialyzed through dialysis bag 1 to obtain preliminary dialysis acid. The preliminary dialysis acid is pre-frozen at -80°C and then freeze-dried to obtain white sponge-like methacrylamide hyaluronic acid.
8. The method for preparing the miR-210@ZIF-8 stress relaxation hydrogel cardiac patch according to claim 7, characterized in that, The specific method for preparing oxidized dextran in step S1 is as follows: S1B-1, prepare a dextran solution with a mass-volume concentration of 100 g / L and a sodium periodate solution with a mass-volume concentration of 100 g / L respectively; S1B-2, under light-protected conditions, the sodium periodate solution is slowly added dropwise to the dextran solution, and the reaction is carried out at room temperature for 4 hours to obtain a preliminary aldehyde reaction solution; S1B-3, the preliminary aldehyde reaction solution is added to a corresponding 1 / 15 volume of ethylene glycol solution, and the oxidation reaction is terminated by stirring to obtain a preliminary solution containing oxidized dextran powder. The preliminary solution containing oxidized dextran powder is placed into dialysis bag 2 for dialysis treatment. After the dialysis is completed, a dialysis concentrate is obtained. The dialysis concentrate is pre-frozen at -80°C and freeze-dried to obtain the oxidized dextran in powder form.
9. The method for preparing a stress-relaxation hydrogel cardiac patch loaded with miR-210@ZIF-8 according to claim 8, characterized in that, The specific method for preparing miR-210@ZIF-8 nanoparticles in step S1 is as follows: S1C-1, using water treated with diethyl pyrocarbonate, prepared 40 mmol / L zinc acetate solution and 1.28 mol / L 2-methylimidazole solution respectively; For S1C-2, according to the volume ratio, take 10 times the volume of a 40 mmol / L zinc acetate solution and add 1 volume of a 20 μmol / L miR-210 solution. After gently mixing, incubate at room temperature for 10 minutes to form Zn. 2+ A mixture that interacts electrostatically with the negatively charged phosphate backbone of miR-210 to form nucleation sites; S1C-3, under rapid stirring, a 1-volume 2-methylimidazole solution with a concentration of 1.28 mol / L is rapidly added to the mixture to form C-3 reaction solution. When the C-3 reaction solution shows turbidity indicating the beginning of the formation of the ZIF-8 coordination structure, the C-3 reaction solution is allowed to stand at room temperature for 20 min to form a preliminary coated nano-liquid that allows miR-210 to be simultaneously coated during the formation of ZIF-8. S1C-4, after the reaction is completed, the preliminary coated nano liquid is centrifuged at 12000 rpm for 15 min, the supernatant is discarded, the precipitate is resuspended in water treated with diethyl pyrocarbonate and washed three times to obtain the miR-210@ZIF-8 nanoparticles. The sodium periodate solution is slowly added dropwise to the dextran solution, and the ratio of sodium periodate to dextran is set at 1:7.6 w / w to 1:3.8 w / w. The final concentration of miR-210@ZIF-8 in the hydrogel bio-ink in S2 is 0.1–1.0 mg / mL; The concentration of the photoinitiator solution in S2 is 2.5% w / v; In step S2, the final concentration of the methacrylamide hyaluronic acid in the hydrogel bio-ink is 2.5% w / v, the final concentration of the gelatin in the hydrogel bio-ink is 3.0% w / v, the final concentration of the oxidized dextran in the hydrogel bio-ink is 1.0% w / v, the final concentration of the photoinitiator in the hydrogel bio-ink is 0.25% w / v, and the final concentration of the miR-210@ZIF-8 nanoparticles in the hydrogel bio-ink is 0.5 mg / mL. The molecular weight cutoff of the dialysis bag 1 is 3500-8000 Da; the isothermal temperature T1 condition is set to 34-40℃; The constant temperature (T1) condition is set to 37°C. The dialysis bag 1 is specifically subjected to dialysis in deionized water for 4 days, with the dialysis solution being changed every 8-12 hours. The dialysis bag 2 is specifically placed in the dialysis bag 2 with a molecular weight cutoff of 3500-8000 Da, and dialyzed in deionized water in the dark for 3 days, with the dialysate changed 4 times a day; The preparation method of methacrylamide hyaluronic acid in step S1 further includes S1A-5, which involves sealing and storing the methacrylamide hyaluronic acid at -20°C for later use. The preparation method of oxidized dextran in step S1 also includes S1B-4, which involves storing the oxidized dextran powder in a light-proof and sealed container. The preparation method of methacrylated hyaluronic acid in step S1 further includes S1A-5, which involves sealing and storing the methacrylated hyaluronic acid at -20°C; the reaction time S is 1.5H to 2.5H.
10. The application of a stress-relaxed hydrogel cardiac patch loaded with miR-210@ZIF-8, characterized in that: It is applied to myocardial repair after myocardial infarction to inhibit excessive mitochondrial division in cardiomyocytes, alleviate hypoxia-related mitochondrial dysfunction, and promote myocardial fibrosis and remodeling.